Akselerasi Pembelajaran Tahfiz Pada Lembaga Pendidikan Al Quran Di Fath Darut Tafsir Sukawangi Bogor - Nasrulloh, Nasrulloh (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research is motivated by the author's interest in three things that are problems regarding learning tahfiz Al-Quran. First, an Al-Quran educational institution with an Al-Quran tahfiz program must prepare professional policies in tahfiz learning strategies and infrastructure so that the goals of Al-Quran tahfiz are achieved as determined. Second, the process of learning tahfiz Al-Quran really requires the right approach, methods and evaluation, so that learning runs well and smoothly without any significant obstacles in achieving success. Third, accelerated learning of Al-Quran tahfiz is really needed by students because there are many branches of knowledge that need to be studied afterwards, both religious knowledge (such as tafsir, fiqh, etc.) or general knowledge. This research aims to (1) analyze the effectiveness of Islamic boarding school leaders' strategies and policies in accelerating the learning of Al-Quran tahfiz. (2) Examining strategies for learning Al-Quran tahfiz at Islamic boarding schools. (3) Finding the main success factors in accelerating learning of Al-Quran tahfiz in Islamic boarding schools.In connection with the problem raised by the author, namely the acceleration of tahfiz learning at Al-Quran educational institutions at the Fath Darut Tafsir Islamic Boarding School, the author uses qualitative research methods at the Fath Darut Tafsir Islamic Boarding School to encourage discipline among students, so that the UTQ Tahfidz Qur'an acceleration program ('Uzlah Tahfidz Qur'an) at the Fath Darut Tafsir Islamic Boarding School runs smoothly. This program was attended by all Islamic boarding school elements from santri & female students, totaling around 150 people, 17 Ustadz & Ustadzah as Musyrif or Musyrifah halaqah of the Qur'an. In the UTQ program, 17 halaqahs will be made for 150 santri and female students with a target of 10 days to get 5 new Juz memorized, and it is hoped that if the students have participated in this UTQ event 6 times they will be able to complete memorizing 30 Juz of the Qur'an.As a result of the UTQ Program, a total of 30 students managed to memorize 5 new juz with a percentage of 20% of the students who took part in the accelerated program. Meanwhile, 15 santri and santriwati managed to memorize more than 5 juz if the percentage was 10%, and those who managed to memorize 4 juz were 40% and less than 4 juz were 30%.